Meta-analysis of programmed cell death 1 polymorphisms with systemic lupus erythematosus risk - Gao, Jie (Oncotarget, 2017)
The association of polymorphisms in programmed cell death 1 (PDCD1) gene with systemic lupus erythematosus (SLE) risk is inconsistent across different studies. This meta-analysis is aimed to provide reliable evidence to the association of five common PDCD1 polymorphisms (PD1.1, PD1.2, PD1.3, PD1.5 and PD1.6) with SLE risk. A total of 28 studies with 4,344 SLE cases and 5,474 healthy controls were included in this meta-analysis. PD1.3 polymorphism was significantly associated with SLE in the overall population (A vs. G: OR = 1.35, 95% CI = 1.12-1.63; GA vs.GG: OR = 1.41, 95% CI = 1.12-1.76; AA+GA vs. GG: OR = 1.41, 95% CI = 1.13-1.7). In the stratified analyses based on ethnicity, we found a significant association in Caucasians and in Mexicans. In the subgroup analyses by gender, a significant association was found between PD1.3 polymorphism and SLE risk in males. The results also suggested an association between the PD1.6 polymorphism and decreased SLE risk (A vs. G: OR = 0.84, 95% CI = 0.73-0.96). Our meta-analysis revealed that PD1.3 polymorphism may increase the susceptibility to SLE, particularly in Caucasians, while PD1.6 may be a protective factor to SLE.